Plastic Antibody of Polypyrrole/Multiwall Carbon Nanotubes on Screen-Printed Electrodes for Cystatin C Detection - Gomes, Rui S. (2021)
This work reports the design of a novel plastic antibody for cystatin C (Cys-C), an acute kidney injury biomarker, and its application in point-of-care (PoC) testing. The synthetic antibody was obtained by tailoring a molecularly imprinted polymer (MIP) on a carbon screen-printed electrode (SPE). The MIP was obtained by electropolymerizing pyrrole (Py) with carboxylated Py (Py-COOH) in the presence of Cys-C and multiwall carbon nanotubes (MWCNTs). Cys-C was removed from the molecularly imprinted poly(Py) matrix (MPPy) by urea treatment. As a control, a non-imprinted poly(Py) matrix (NPPy) was obtained by the same procedure, but without Cys-C. The assembly of the MIP material was evaluated in situ by Raman spectroscopy and the binding ability of Cys-C was evaluated by the cyclic voltammetry (CV) and differential pulse voltammetry (DPV) electrochemical techniques. The MIP sensor responses were measured by the DPV anodic peaks obtained in the presence of ferro/ferricyanide. The peak currents decreased linearly from 0.5 to 20.0 ng/mL of Cys-C at each 20 min successive incubation and a limit of detection below 0.5 ng/mL was obtained at pH 6.0. The MPPy/SPE was used to analyze Cys-C in spiked serum samples, showing recoveries <3%. This device showed promising features in terms of simplicity, cost and sensitivity for acute kidney injury diagnosis at the point of care.